Full geometry optimizations of the mixed‐valence CaMn4O4X(H2O)4 (X=OH or O) cluster in OEC of PS II: Degree of symmetry breaking of the labile Mn‐X‐Mn bond revealed by several hybrid DFT calculations. Issue 4 (13th April 2012) - Yamaguchi, K.; Isobe, H.; Yamanaka, S.; Saito, T.; Kanda, K.; Shoji, M.; Umena, Y.; Kawakami, K.; Shen, J.‐R.; Kamiya, N.; Okumura, M.; Nakai, Hiromi; et al.
Abstract Several hybrid DFT methods were applied to full geometry optimizations of the CaMn4O4X(H2O)4 (XOH1− (1) or O2− (2)) cluster in the oxygen evolving complex (OEC) of photosystem II (PSII) to elucidate Mn‐Mn, Mn‐Ca, and Mn‐O distances on a theoretical ground. The computed Mn‐Mn distances were compared with previous (London and Berlin) X‐ray diffraction (XRD), and Berkeley and Berlin EXAFS results, together with the recent high‐resolution XRD structure by Umena and coworkers. Present computational results by the hybrid DFT methods have elucidated several differences among these accumulated results. These DFT results led us to reassign the Mn‐Mn and Mn‐Ca distances by the EXAFS experiments, which became consistent with the results obtained by the high‐resolution XRD structure. A characteristic feature revealed via the optimized Mn‐O distances was that the degree of symmetry breaking of the Mn1‐O(57)‐Mn4 bond is not so remarkable under the UBHandHLYP approximation but it can be large by other hybrid DFT methods. The computational results for 2 indicated reduction of the Mn3‐Mn4 distance with the deprotonation of the bridging oxo group. The hybrid DFT results for 1 are not inconsistent with an experimental proposal based on the new XRD structure, namely a protonated μ3‐oxygen at the internal O(57) site of the cluster in the S1 state. On the other hand, the reduction of Mn ions (not degradation of whole cluster structure) by the X‐ray irradiation still remains an important issue for refinements of the XRD structure. The computational results are discussed in relation to those of the electron spin echo envelope modulation (ESEEM) and possible pathways for water splitting reaction. Implications of the present DFT structures are discussed in relation to the previous DFT and related computational results, together with recent XRD results for cubane‐like model clusters for OEC of PSII. © 2012 Wiley Periodicals, Inc.